The migrant memory: Les urnes scellées by Emile Ollivier - Kunešová, Květuše (Romanica Olomucensia, 2019)
This article deals with the motifs of the present and the past in the work of Emile Ollivier, a modern Quebecois writer of Haitian origin, whose texts are permeated by images that pertain, on the one hand, to his exile in Canada and, on the other hand, to the picture of the native country as a souvenir. The problematics of temporality and memory are analyzed in detail by Paul Ricœur in his works Temps et récit and La mémoire, l'histoire, l'oubli, which are thus chosen as the main methodological references of this paper. In migrant literature, however, temporality is closely related to spatiality, as has been noted by Quebecois literary theorists, e.g. Simon Harel, which forms the second methodological point of departure of the study. The memory can be considered as a dynamic force in the text of the novel Les urnes scellées. A couple of Haitian emigrants, returning from Canada to their homeland after twenty-five years of exile, experience a harsh constrast between their memories and reality. Adrien's profession as an archaeologist nevertheless impels him to search for the past. He is obsessed by searching for the circumstances of a murder. In spite of the fact that his hunt for the murderer is in vain, Adrien uncovers a network of secrets and memories of the community, realizing how difficult it is to find his own roots. The analysis reveals that in the case of Les urnes scellées memory is closely connected to space, not only in individual cases, but also on a higher level, that of the country. The collective memory of Haiti finally appears as a part of message of the novel, the other part of which is the search for personal and national identity.
Keywords: Quebecois literature; migrant literature; exile; Haiti; memory